Arabidopsis Contains at Least Four Independent Blue-Light-Activated Signal Transduction Pathways - Lascève, Gérard (American Society of Plant Physiologists, 1999)
We have investigated the stomatal and phototropic responses to blue light of a number of single and double mutants at various loci that encode proteins involved in blue-light responses in Arabidopsis. The stomatal responses of light-grown mutant plants (cry1, cry2, nph1, nph3, nph4, cry1cry2, and nph1cry1) did not differ significantly from those of their wild-type counterparts. Second positive phototropic responses of etiolated mutant seedlings, cry1, cry2, cry1cry2, and npq1-2, were also similar to those of their wild-type counterparts. Although npq1 and single and double cry1cry2 mutants showed somewhat reduced amplitude for first positive phototropism, threshold, peak, and saturation fluence values for first positive phototropic responses of etiolated seedlings did not differ from those of wild-type seedlings. Similar to the cry1cry2 double mutants and to npq1-2, a phyAphyB mutant showed reduced curvature but no change in the position or shape of the fluence-response curve. By contrast, the phototropism mutant nph1-5 failed to show phototropic curvature under any of the irradiation conditions used in the present study. We conclude that the chromoproteins cry1, cry2, nph1, and the blue-light photoreceptor for the stomatal response are genetically separable. Moreover, these photoreceptors appear to activate separate signal transduction pathways.